MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PEMANGKASAN RAMBUT DASAR KOMPETENSI KEAHLIAN TATA KECANTIKAN RAMBUT SMK N 3 PAYAKUMBUH - Annisa, Sharen; Rahmiati, Rahmiati; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The purpose of this study was to obtain an overview of student motivation in following subjects basic hair cuts, which include indicators of (a) the passion and desire to excel in learning, (b) the need to learn, (c) the hopes and aspirations of the future in basic hair cuts. This research is descriptive quantitative. Population and samples in this study were all students of class X and XI competency skills hairstyling SMK N 3 Payakumbuh totaling 38 people. Data were obtained using a questionnaire as the instrument that has been on test validity and reliability. The results are presented in the form of frequency distribution and percentage rates. The results obtained by achieving an average score of respondents terhap indicators passion and desire in learning achievement in the category of less Once with (68.42%). Indicators of the level of achievement in the Learning Needs Basic Hair Trimming should be in the category of less (47.36%). While indicators of expectations and aspirations of future levels of achievement in the category of Medium respondents (36.84%). In keseluruah motivation to study the basic hair cuts are at once less category (36.84%).